Annexin A2 regulates Mycoplasma bovis adhesion and invasion to embryo bovine lung cells affecting molecular expression essential to inflammatory response - Zhang, Hui; Lu, Doukun; Zhang, Yiqiu; Zhao, Gang; Raheem, Abdul; Chen, Yingyu; Chen, Xi; Hu, Changmin; Chen, Huanchun; Yang, Liguo; Guo, Aizhen (Frontiers in Immunology, 2022)
Mycoplasma bovis (M. bovis) is an important pathogen of the bovine respiratory disease complex, invading lower respiratory tracts and causing severe pneumonia. However, its molecular mechanism largely remains unknown. Host annexin A2 (ANXA2) is a calcium-dependent phospholipid-binding protein. The current study sought to determine whether ANXA2 could mediate M. bovis adhesion and invasion thereby affecting its induction of inflammatory response. ANXA2 expression was upregulated in M. bovis-infected bovine lung epithelial cells (EBL), and blocking ANXA2 with an anti-ANXA2 antibody reduced M. bovis adhesion to EBL. Compared with uninfected cells, more ANXA2 was translocated from the cytoplasm to the cell surface after M. bovis infection. Furthermore, RNA interference knockdown of ANXA2 expression in EBL cells resulted in a significant decrease in M. bovis invasion and F-actin polymerization. Next, the transcriptomic study of M. bovis-infected EBL cells with and without ANXA2 knockdown were performed. The data exhibited that ANXA2 knockdown EBL cells had 2487 differentially expressed genes (DEGs), with 1175 upregulated and 1312 downregulated compared to control. According to GO and KEGG analyses, 50 genes potentially linked to inflammatory responses, 23 involved in extracellular matrix (ECM) receptor interaction, and 48 associated with PI3K-AKT signal pathways were upregulated, while 38 mRNA binding genes, 16 mRNA 3′-UTR binding genes, and 34 RNA transport genes were downregulated. Furthermore, 19 genes with various change-folds were selected for qPCR verification, and the results agreed with the RNA-seq findings. Above all, the transcription of two chemokines (IL-8 and CXCL5) and a key bovine β-defensin TAP in IL-17 signaling pathway were significantly increased in ANXA2 knockdown cells. Moreover, ANXA2 knockdown or knockout could increase NF-κB and MAPK phosphorylation activity in response to M. bovis infection. Additionally, ANXA2 knockdown also significantly decreased the CD44 transcripts via exon V3 and V7 skipping after M. bovis infection. We concluded that M. bovis borrowed host ANXA2 to mediate its adhesion and invasion thereby negatively regulating molecular expression essential to IL-17 signal pathway. Furthermore, CD44 V3 and V7 isoforms might contribute to this ANXA2 meditated processes in M. bovis infected EBL cells. These findings revealed a new understanding of pathogenesis for M. bovis infection.